1992
DOI: 10.1136/bmj.305.6862.1124
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for efficacy of drugs affecting bone metabolism in preventing hip fracture.

Abstract: Objective-To examine the effects of taking drugs affecting bone metabolism on the risk of hip fracture in women aged over 50 years.Design-Retrospective, population based, casecontrol study by questionnaire.Setting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
4

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(74 citation statements)
references
References 19 publications
3
67
0
4
Order By: Relevance
“…87 In the last three decades, calcitonin has been used in postmenopausal women to prevent bone loss 88 and reduce pathological fractures. 89 Transcutaneous injection or intranasal intake of salmon calcitonin has been reported to limit immobilization hypercalcemia and hypercalciuria, 40,90,91 to reduce osteoclast activity, 90 and to preserve trabecular bone volume. 90 But a high incidence of nausea and the frequency of injections seem to limit patient compliance.…”
Section: Calcitoninmentioning
confidence: 99%
“…87 In the last three decades, calcitonin has been used in postmenopausal women to prevent bone loss 88 and reduce pathological fractures. 89 Transcutaneous injection or intranasal intake of salmon calcitonin has been reported to limit immobilization hypercalcemia and hypercalciuria, 40,90,91 to reduce osteoclast activity, 90 and to preserve trabecular bone volume. 90 But a high incidence of nausea and the frequency of injections seem to limit patient compliance.…”
Section: Calcitoninmentioning
confidence: 99%
“…(1)(2)(3)(4) Previous studies about HRT and nonvertebral fractures are few and have mostly been performed on elderly women (5,6) or have examined hip fracture risk related to HRT. (7)(8)(9)(10) The effect of HRT on fractures in younger women is less established. (11,12) Forearm fracture is the most common fracture in early postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Two randomised controlled prospective studies 24,64 and a retrospective study 37 have examined the effects of calcium and vitamin D supplementation on osteoporotic fracture incidence. In the epidemiological case-control study conducted in six European Mediterranean countries (MEDOS study) treatment with vitamin D has been reported to be associated with a reduced incidence of hip fracture 37 .…”
Section: Vitamin D Status and Bone Healthmentioning
confidence: 99%
“…In the epidemiological case-control study conducted in six European Mediterranean countries (MEDOS study) treatment with vitamin D has been reported to be associated with a reduced incidence of hip fracture 37 . The first prospective study was performed on a French cohort of over 3000 institutionalised elderly women (mean age 84 years) during treatment with either vitamin D (800 IU/day) and calcium (1.2 gr/day) or placebo for three years 64 .…”
Section: Vitamin D Status and Bone Healthmentioning
confidence: 99%